A flórula fanerogâmica das restingas do estado do Pará. I - Ilhas de Maiandeua e Algodoal. família malpighiaceae - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1995)
Maiandeua and Algodoal are islands of the coast of Pará situated in the municipal district of Maracanã at about 00 34'45" to 00 34'12" latitude and 4731'05" to 47 34'12" longitude W. In the sandbanks of these islands the Malpighiaceae family is represented by the species Byrsonima crassifolia H.B.K. and Tetrapteris mucronata Cavo. Morphological observations were made under a ZEISS stereomicroscope with a clear camera. The nomenclature used to indicate the shape and indentation of morphological structures was based on the works of LAWRENCE (1973), RADFORD et al (1974) and RIZINNI (1977). Byrsonima crassifolia H.B.K., a shrub with a woody, cylindrical stem, with a star-shaped indumentum, elliptic, opposite leaves; racemose inflorescence with hermaphrodite flowers. Tetrapteris mucronata Cav., a branched liana with a woody, cylindrical stem, with a star-shaped indumentum, elliptic, opposite leaves; umbel-shaped inflorescence with hermaphrodite flowers (CNPq/MPEG).
The phanerogamous flora of the restingas of the state of Pará. I - Maiandeua and Algodoal islands. malpighiaceae family
Keywords: Flórula; Restinga; Maiandeua; herbário; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA